Barriers to healthcare professionals screening, recognizing, and managing delirium in the adult patients receiving specialist palliative care: a mixed-methods systematic review - Fang Qian; Danyang Yao; Huanhuan Shi; Tao-Hsin Tung; Dongjun Bi (BMC Palliative Care)
Abstract Background Delirium frequently occurs in palliative care settings, yet its screening, identification, and management remain suboptimal in clinical practice. This review aims to elucidate the barriers preventing healthcare professionals from effectively screening, recognizing, and managing delirium in adult patients receiving specialist palliative care, with the goal of developing strategies to enhance clinical practice. Methods A mixed-methods systematic review was conducted (PROSPERO: CRD42024563666). Literature was sourced from PubMed, Web of Science, Embase, CINAHL, The Cochrane Library, and Clinical Trials databases from their inception to November 16, 2024, without language restrictions. Studies that were primary quantitative, qualitative, and mixed-methods research, and reported the barriers to healthcare professionals’ screening, recognition, and management of delirium in adult patients receiving specialist palliative care (including inpatient hospice/hospital care, consultation teams, and outpatient/community services) were included. Studies were excluded if they did not permit barrier factor extraction, had duplicate or incomplete data, or were case reports or conference abstracts. The Mixed Methods Appraisal Tool (MMAT) version 2018 was employed to evaluate the methodological quality of included studies. Data synthesis used the convergent-integrated JBI mixed-methods approach. Results 21 articles that meet the selection criteria have been identified, with 11 quantitative, 8 qualitative and 2 mixed-methods, collectively involving 857 patients and 649 healthcare professionals. Four themes were identified from the includes studies: (1) Individual level: knowledge and understanding gaps among healthcare professionals; (2) Operational level: implementation challenges in clinical practice; (3) Organizational level: structural and resource deficiencies; (4) Contextual level: specific impacts of situational factors. Conclusion The systematic review uncovered a complex interplay of barriers spanning individual, operational, organizational, and contextual levels in palliative settings. To address these challenges, recommended strategies include developing targeted training programs, implementing standardized delirium assessment tools, improving guideline accessibility, and promoting interdisciplinary collaboration to enhance delirium screening and management in palliative care.